1986
DOI: 10.1677/joe.0.1090239
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress effects over two generations in rats

Abstract: Persistent effects of stress were found in second generation rats bred from females whose own mothers had been stressed during pregnancy. The second generation rats grew more slowly, with a plateau in the growth being reached at the same age as in the controls. This resulted in adult animals of both sexes being permanently smaller than their control counterparts. When these offspring were subjected to short-term stress (one session) in adulthood, the response was not significantly different to that for the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…This increase in mortality was due to the surgery itself rather than the speci®c treatment: nearly all of the mortality occurred within a few days of surgical implantation, and the number of females that died did not dier signi®cantly between treatments. Surgical implantation also increased clutch abortion in comparison to non-implanted females, but the rate of abortion did not dier signi®cantly between B-and P-implanted females as found in other species (Pollard 1984(Pollard , 1986Wilson & Wing®eld 1992). Overall, surgical implantation approximately doubled mortality and the incidence of abortion in comparison to natural conditions.…”
Section: E F F E C T O F I M P L a N T A T I O Nmentioning
confidence: 58%
“…This increase in mortality was due to the surgery itself rather than the speci®c treatment: nearly all of the mortality occurred within a few days of surgical implantation, and the number of females that died did not dier signi®cantly between treatments. Surgical implantation also increased clutch abortion in comparison to non-implanted females, but the rate of abortion did not dier signi®cantly between B-and P-implanted females as found in other species (Pollard 1984(Pollard , 1986Wilson & Wing®eld 1992). Overall, surgical implantation approximately doubled mortality and the incidence of abortion in comparison to natural conditions.…”
Section: E F F E C T O F I M P L a N T A T I O Nmentioning
confidence: 58%
“…Pollard [154] demonstrated that stress effects were persistent in second-generation rats bred from females whose own mothers had been stressed during pregnancy. It is noteworthy that these effects persisted into adulthood [154]. Daughters of physically stressed mothers are less fertile and less fecund than daughters of unstressed mothers [157,176,177].…”
Section: Hormones and Maternal Effectsmentioning
confidence: 99%
“…Under laboratory conditions, Mihok and Boonstra (1992) showed that the prior experience of decline-phase female meadow voles (Microtus pennsylvanicus) had long-term detrimental consequences for the performance of the next two generations. Laboratory studies have shown that a variety of pre-and postnatal stresses can have long-lasting effects and impair reproductive performance for one or two generations (Pollard 1986;Boonstra 1994). Similarly, in a field study, Mech et al (1991) showed that the mass and survival of fawns of white-tailed deer (Odocoileus virginianus) were directly correlated with maternal nutrition during gestation.…”
Section: Increased Physiological Stressmentioning
confidence: 99%